Business Opportunity Analysis in ROW Land Utilization at Western Java Area, PT. Pertamina Gas (Case Study: PT Cipta Energy) (The Indonesian Journal of Business Administration, 2014)
Abstact - Western Java Area (WJA) is one of the operation area of PT . Pertamina Gas that currently responsible for managing and operating assets that exist in the western java area. Given today's gas business development especially in the Western Java Area, Banten and Jakarta very rapidly, especially in line with Government policy whereby natural gas into alternative fuels as a substitute for fuel oil price is higher today while its reserves are very low, many parties especially entrepreneurs or business in the gas industry , are racing to build gas infrastructure to meet the gas demand in the industrial zones in the regions of West Java and Banten in particular and gas needs in the Jakarta area. With businesses becoming increasingly difficult to obtain land for the installation of firm gas infrastructure, then there is a business opportunity in the Western Java Area to increase the revenue of the land utilize is through a profit sharing by allocating land ROW value as equity capital in the form of participating. The methodology used PESTEL Analysis, SWOT Analysis, Supply/Demand Analysis, and 5-forces Analysis. From these analysis, then performed economic calculation that focused at PT.XYZ in Bitung Gas Pipeline Project.From the analysis and calculation performed concluded that by changing patterns of land rental rates by a third party to build a business-related infrastructure Pertagas of the original using the base "50% of SVTO" into "profit sharing" will provide increased revenues larger company. From case studies conducted successfully obtained a profit of 1.5 times Keywords : land utilization, sharing profit, market value.